2020
DOI: 10.1186/s13570-020-00178-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pastoral contexts in the greater Horn of Africa: Implications and recommendations

Abstract: COVID-19 is a global pandemic that continues to spread around the world, including to Africa where cases are steadily increasing. The African Centres for Disease Control and Prevention is leading the pandemic response in Africa, with direction from the World Health Organization guidelines for critical preparedness, readiness, and response actions. These are written for national governments, lacking nuance for population and local differences. In the greater Horn of Africa, conditions unique to pastoralists suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Specifically, Figure 6 indicates that the majority of the reviewed articles focused on the ‘absorbance’, i.e., the capacity of livestock systems to limit the impact of the COVID-19 pandemic ( n = 51), and the ‘recovery’, i.e., the ability of livestock systems to return to their original state following the pandemic ( n = 48), of livestock systems. Articles cited in the previous sub-section of this paper belong mainly to these two phases of resilience, where the focus has been on how livestock systems were affected by- and responded to the COVID-19-induced risks, such as decreased farm productivity, reduced access to consumer and input markets, shortage of farm labor, reduced consumers’ purchasing power and vulnerability of market prices, to cite a few [ 1 , 22 , 35 , 40 , 58 ]. Based on the investigation of these risks and their effects, the reviewed literature turns then to focus on immediate and short-run countermeasures implemented mainly by governments and actors within livestock supply chains to mitigate the impact of the pandemic and restore the ability of livestock systems to return to their original state and resume livestock activities along the supply chain [ 40 , 59 , 60 , 61 ].…”
Section: Results and Synthesis Of Evidencementioning
confidence: 99%
“…Specifically, Figure 6 indicates that the majority of the reviewed articles focused on the ‘absorbance’, i.e., the capacity of livestock systems to limit the impact of the COVID-19 pandemic ( n = 51), and the ‘recovery’, i.e., the ability of livestock systems to return to their original state following the pandemic ( n = 48), of livestock systems. Articles cited in the previous sub-section of this paper belong mainly to these two phases of resilience, where the focus has been on how livestock systems were affected by- and responded to the COVID-19-induced risks, such as decreased farm productivity, reduced access to consumer and input markets, shortage of farm labor, reduced consumers’ purchasing power and vulnerability of market prices, to cite a few [ 1 , 22 , 35 , 40 , 58 ]. Based on the investigation of these risks and their effects, the reviewed literature turns then to focus on immediate and short-run countermeasures implemented mainly by governments and actors within livestock supply chains to mitigate the impact of the pandemic and restore the ability of livestock systems to return to their original state and resume livestock activities along the supply chain [ 40 , 59 , 60 , 61 ].…”
Section: Results and Synthesis Of Evidencementioning
confidence: 99%
“…For example, a study in Spain reported that, although small ruminants are not sanitary affected by this virus, global data evidenced a lamb price drop ranging from 16.8% to 26.9% and a 12.5% to up to 40% drop in the goat kid meat market ( Vidaurreta et al, 2020 ). Some have also reported that decreased access to pastoral areas due to COVID-19 measures will impact desert locust control, disaster relief or disease control ( Griffith et al 2020 ). Livestock has various types of value, and the costs have not only been economical, but also supporting livelihoods ( Griffith et al 2020 ) as well as at the emotional value and animal bond level.…”
Section: Resultsmentioning
confidence: 99%
“…Some have also reported that decreased access to pastoral areas due to COVID-19 measures will impact desert locust control, disaster relief or disease control ( Griffith et al 2020 ). Livestock has various types of value, and the costs have not only been economical, but also supporting livelihoods ( Griffith et al 2020 ) as well as at the emotional value and animal bond level. The emotional impact of the pandemic on farmers ( Hafez & Attia, 2020 ) and how these impacts on animal welfare is an area that also merits attention as part of any pandemic management and recovery phases.…”
Section: Resultsmentioning
confidence: 99%
“…The population in Teso sub-region is estimated at about 2.4 million people with a total land coverage of about 14,855 sq. km (UBOS 2014 ). While the population in Karamoja sub-region is estimated at about 1.2 million people (pastoralists), with a total land coverage of more than 27,000 sq.…”
Section: Study Areamentioning
confidence: 99%
“…Livestock contributes to people’s livelihoods through numerous channels such as income, food, employment, draft power, hauling services, manure, social status, savings, and insurance, among others (Nyariki and Amwata 2019 ). For livestock keepers including pastoralists who rely mainly on livestock rearing with mobile herds (Griffith et al 2020 ), and agro-pastoralists (crop and livestock farmers) whose livelihood strategy is dependent on keeping livestock, in East Africa access to livestock markets is an essential component of their livelihood (Aklilu and Catley 2010 ; Lynch 2020 ; Roba et al 2017 ). Livestock traders play a significant role in the livestock value chains by linking producers, processors, and consumers, thus acting as lifeblood for pastoralists whose areas are remote, less accessible, and sometimes insecure due to cattle raids (Aklilu 2017 ; Roba et al 2019 ; Roba et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%